POTENTIAL OF CURCUMA LONGA EXTRACT TO THE GROWTH OF SALMONELLA STAPHYLOCOCCUS AND BACILLUS SUBSTILIS ON PELOR EXTRACT - Astuti, Siswi; Rahman, Nanik Astuti; Rastini, Endah Kusuma (Journal of Sustainable Technology and Applied Science (JSTAS), 2020)
People with autism are sensitive to milk protein (casein), gluten, and sugar. These foods can cause an increase in aggressive behavior, crying, anger, stress and depression, while also able to increase digestive disorders, allergies and neurobiological disorders in people with autism. Trials have been carried out on several autistic people by providing food based on MOCAF modified with Centella Asiatica extract with positive results. Children are more focused, more communicative and the symptoms of stress and depression decrease. The weakness is that it can still lack the necessary vitamins and minerals so that it is continued with the manufacture of supplements made from Centella Asiatica and egg extracts (PELOR). Those contain vitamins and minerals needed by people with autism and do not form new compounds but still contain microbes. The research was done by giving various concentrations of 5%, 10%, 15%, 20%, 25%, 30% and 35% curcuma longa in pelor extract which is expected to reduce microbial growth. The results concluded that PELOR extract with the addition of 20% curcuma longa can kill the growth of harmful microorganisms of Salmonella and Staphylococcus but it is still not effective in inhibiting the growth of Bacillus substilis. In the addition of 20% curcuma longa, there was Bacillus substilis with a total of 3 x103 colonies/100ml or an NPN value of 0.03 has met the SNI 7388: 2009 standard. Therefore, it was concluded that it was safe to potentially be a balanced nutritious supplementary food needed by people with autism.